Long-Lasting In Situ Forming Implant Loaded with Bupivacaine: Investigation on Polymeric and Non-Polymeric Carrier and Solvent Effect - Bazraee, Saeed; Mobedi, Hamid; Mashak, Arezuo; Jamshidi, Ahmad (Current Drug Delivery, 2022)
Introduction: Typically, in situ forming implants utilize Poly (lactide- co- glycolide) (PLGA) as carrier and N-methyl-2-pyrrolidone (NMP) as solvent. However, it is essential to develop different carriers to release various drugs in a controlled and sustained manner with economic and safety considerations. Objective: The present study aims to evaluate the in-vitro release of Bupivacaine HCl from in situ forming systems as post-operative local anesthesia. Methods: We used Sucrose acetate isobutyrate (SAIB), PLGA 50:50, and a mixture of them as carriers to compare the release behavior. Besides, the effect of PLGA molecular weight (RG 502H, RG 503H, and RG 504H), solvent type, and solvent concentration on the drug release profile has been evaluated. The formulations were characterized by investigating their in-vitro drug release, rheological properties, solubility, and DSC, in addition to their morphological properties. Furthermore, the Korsmeyer-Peppas and Weibull models were applied to the experimental data. Results revealed that using a mixture of SAIB and PLGA compared to using them solely can extend the Bupivacaine HCl release from 3 days to two weeks. Results: The DSC results demonstrated the compatibility of the mixture by showing a single Tg. The formulation with NMP exhibited a higher burst release and final release in comparison with other solvents by 30% and 96%, respectively. Increasing the solvent concentration from 12% to 32% raised the drug release significantly, which confirmed the larger porosity in the morphology results. From the Korsmeyer-Peppas model, the mechanism of drug release has been predicted to be non-Fickian diffusion.
Keywords: drug delivery systems